METHODS FOR IMPLEMENTING NEW PROJECTS BASED ON PEDAGOGICAL MECHANISMS IN DEVELOPING PROFESSIONAL COMPETENCE AND CREATIVITY OF FUTURE ENGINEERS - Badalov Utkirbek Nomoz ogli, (PEDAGOGS, 2025)
Abstract: the development of professional competence and creativity among future engineers is crucial in preparing them for real-world challenges. This paper explores the pedagogical mechanisms that contribute to fostering these qualities and examines innovative methods for integrating new projects into engineering education. The study highlights project-based learning, interdisciplinary approaches, and technological integration as key strategies in enhancing the competence and creativity of engineering students